ANALISIS KONVERSI LAHAN PERTANIAN SAWAH KE NON PERTANIAN KABUPATEN ACEH BESAR - Riska Nurmalinda; Muhammad Abrar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
AbstractThis study aims to determine the conversion of lowland agricultural land in Aceh Besar District. The variables in this study include the number of industries, population, and length of roads. In this study the authors used quantitative descriptive analysis methods, with secondary data obtained from related agencies with the 2005-2019 observation year. Data analysis used multiple linear regression models (multiplier linear regression). The results showed that partially the variable number of industries (IN) had a negative and insignificant effect, the population variable (PD) had a negative and significant effect, while the road length variable (JL) had a positive and significant effect on the conversion of paddy fields in Aceh Besar District.Keywords: Conversion of paddy fields, industry, population, road length